Boosting the Bifunctional Oxygen Electrode Activity of Nitrogen-decorated Carbon Networks via Ni/NiO Addition for Li-Air and Zn-Air Batteries. Issue 3 (1st March 2023) - Athika, Mattath; Junais, Pulikkathumbayil Muhammed; Elumalai, Perumal
Abstract : Designing efficient and cost-effective oxygen electrode catalysts for metal-air batteries is the most intrinsic requisite for next-generation energy storage devices. In this work, bifunctional air-breathing electrode catalysts made of nitrogen-doped carbon (NC) and nickel/nickel oxide/nitrogen-doped carbon (NNONC) nanocomposites are explored for rechargeable Li-Air and Zn-Air batteries. The integration of Ni/NiO nanoparticles on the NC enhances the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) activities of the NC. Ni, nickel oxide, and NC acted synergistically to create additional reaction sites, high conductivity, and rapid diffusion pathways, resulting in increased catalytic activity. The CR-2032 coin-type and split cell Li-Air batteries were made with NNONC composite as cathode and Lithium metal as anode. The split cell had a high discharge capacity of 3330 mA h g −1 at a current density of 100 mA g −1 . Moreover, the NNONC used as bifunctional cathode catalyst in the rechargeable Zn-Air battery. Where Anode is made of zinc-can from a used zinc carbon battery. The Zn-Air battery has good electrochemical activity, such as good cycle life and low overpotentials of 0.31 and 0.19 V for charging and discharging, respectively. Thus, NNONC can be a promising bifunctional catalyst for both the non–aqueous and aqueous rechargeable metal–air batteries.